Anatomy and evolution of a migmatite-cored extensional metamorphic dome and interaction with syn-kinematic intrusions, the Mykonos-Delos-Rheneia MCC. (March 2021) - Jolivet, Laurent; Sautter, Violaine; Moretti, Isabelle; Vettor, Tommy; Papadopoulou, Zozi; Augier, Romain; Denèle, Yoann; Arbaret, Laurent
Highlights: The structure of the Mykonos-Delos-Rheneia core complex is described. Interactions of a granitic pluton and a migmatite a-type dome. Evolution of a MCC from migmatites to supra-detachment basin. Abstract: Post-orogenic extension in back-arc regions is classically associated with metamorphic core complexes (MCCs) cored with exhumed metamorphic rocks and granitic intrusions interacting with low-angle detachments. When additional heat is provided by the advected asthenosphere below the extending region, for instance above slab tears, high-temperature migmatite-cored metamorphic domes and composite intrusions are emplaced whose geometry and kinematics of emplacement are controlled by regional extension and by detachments. The Cyclades Archipelago (Aegean Sea) hosts several such Miocene high-temperature MMCs intruded by Miocene granitoids, offering windows open on the interactions of intrusions with the Livada and Mykonos detachments, two branches of the North Cycladic Detachment System. Deformation associated with North Cycladic Detachment System has been described detailed on Mykonos based on a structural study of the deformation of the Mykonos pluton, but the high-temperature gneiss core of the MCC and the root zone of the intrusion have received little attention. Based on field surveys of the neighboring islands of Rheneia and Delos, we propose in this paper a new geological map and show that the locally migmatitic core of the MCC that extends from Rheneia to the Apollonia peninsula on Mykonos, is topped by a 500 m-thick low-angle shear zone, the Rheneia Shear Zone, coeval with the intrusion of a series of granitoids evolving from granodiorite to monzogranite. The Rheneia Shear Zone shows progressive flattening and shearing, with a constrictional component, during the intrusion of numerous fine-grained felsic dykes at various stages that are totally transposed to become parallel to the main regional foliation. The migmatitic core and the intrusion are intensely stretched with an E–W trending lineation and folds with axes parallel to the lineation. Structural compatibility between the migmatites and the intrusion show that the rheological parameters were not much different at the time of intrusion. The same deformation continued during cooling of the dome while new batches of granitic material intruded the colder gneiss. The granites show syn-kinematic stretching at the magmatic stage and after cooling, leading to full homoaxiality between the magmatic fabric and the mylonites below the Livada and Mykonos Detachment. From the stage of lower crustal partial melting and subsequent intrusion to mylonitization and formation of the brittle Mykonos detachment, deposition of the supra-detachment Miocene sediments and the late intrusion of baryte-iron dykes, the same kinematics is observed until a change in the stress regime some 9 Ma ago. The Mykonos-Delos-Rheneia MCC illustrates the continuous interactions between a detachment system and a growing pluton and how a discrete magmatic event can be influenced by long-term tectonics.